Sheltered from the Waves : "Discernment" according to Diadochus of Photike - Singh Mesconi, Carlos, (Patristic Studies in Global Perspective ;, 2026)
Learning to discern God's will amidst false paths and temptations is essential to the Christian life. This inner struggle often creates feelings of instability, figuratively casting us into the turbulent sea of discernment-a fluctuating landscape that heightens the navigator's crisis in the face of threatening storms. Yet, when we find refuge "sheltered from the waves," we can sail toward the harbor of God's will. The core of this monograph presents the concept of διάκρισις in Diadochus of Photike as a pivotal element for understanding his Work. Readers will encounter the profound insights of a monk who, through the "university of the desert," serves as a spiritual master, guiding us to know and practice the art of discerning.